Assisted ultrasonic wave of vanillin derivatives synthesis and antioxidant activity using DPPH method - Retnosari, Rini; Sari, Karina Kurnia; Marfu'ah, Siti; Sutrisno; Rachman, Ihsan Budi (Communications in Science and Technology, 2022)
In recent years, the need for compounds with antioxidant activities have expanded. Generally, the natures of these compounds involve the presence of conjugated double bonds, phenolic groups, and resonance effects on the structure. One of the compounds with the phenolic group is vanillin. It can be modified into the derivative of 1,8-dioxo-octahydroxantene compound due to its aldehyde content. Meanwhile, 1,8-dioxo-octahydroxantene compound has two 2- cyclohexenone rings bound in the pyran ring and one phenolic group, expected to carry more excellent antioxidant activity than vanillin. The 9-(4-hydroxy-3-methoxyphenyl)-3,4,5,6,7,9- hexahydro -1H-xantene-1,8(2H)-dione (Compound 1) was synthesized from 1,3- cyclohexanedione and vanillin through Knoevenagel's condensation reaction aided with an acid catalyst with a single reaction phase. Besides, green chemistry was adopted in this study using environmentally friendly catalysts from lime juice and ultrasonic wave. The synthesized compounds' structure was confirmed through the spectrophotometer IR, GC-MS, and 1H-NMR spectrometer, while its antioxidant activity was tested using the DPPH method. The reaction occurred with and without lime juice catalyst, producing yields of 6.65% and 70.58%, respectively. The results of the antioxidant activity test suggest that Compound 1 carries substantially robust antioxidant activities, with IC50 of 0.99 ppm.